Evidence of ingested plastics in stranded loggerhead sea turtles along the Greek coastline, East Mediterranean Sea. (August 2020) - Digka, Nikoletta; Bray, Laura; Tsangaris, Catherine; Andreanidou, Konstantina; Kasimati, Eirini; Kofidou, Evangelia; Komnenou, Anastasia; Kaberi, Helen
Abstract: Plastic debris has become a major threat to the marine environment and wildlife. Sea turtles are particularly vulnerable, and are known to ingest plastic debris globally; however, information from Greek waters is still absent. In this study, 36 stranded dead loggerhead turtles ( Caretta caretta ) were collected from the Greek coastline area, and their gastrointestinal content was analysed for ingested plastic debris. Twenty-six individuals (72%) were found to have ingested plastic, with an average of 7.94 ± 3.85 (SE) plastic items per turtle. In total, 286 plastic items were counted and categorised by size, shape, colour, and polymer type. Fourier Transform Infrared Spectrometry revealed that polypropylene and polyethylene were the dominant polymer plastic types found. Results indicated a variation in plastic ingestion amongst life stages of the loggerhead specimens. This study provides evidence of plastic ingestion by loggerhead turtles in Greek waters. Graphical abstract: Image 1 Highlights: Plastic ingestion by sea turtles investigated for the first time in Greek waters. 72% of the loggerheads were found to have ingested plastics. Plastic ingestion varies along sea turtles' life stages. Higher levels of sinking polymers (PET, Nylon) in adult specimens. Abstract : High occurrence (72%) of plastic ingestion in Loggerhead Sea turtles along the Greek coastline and variations in levels of ingested plastics amongst sea turtles' life stages.